Elemen-Elemen Yang Terkait Dengan Customer Satisfaction - Ramadhan, M Affan Alfi Syahri; Danibrata, Aulia (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
This study aims to determine whether there is an influence of utilitarian value, hedonic value, social value, and perceived risk on the customer satisfaction for Shopee application users in Jabodetabek The object used in this research is the Shopee application. The method used for sample selection in this research is using purposive sampling method and taken as many as 103 data that meet the research criteria and the data obtained from data collection using a questionnaire distribution. The method used in this study is the statistical calculation of multiple regression analysis. The results of this study showed that utilitarian value, hedonic value, social value, and perceived risk had an effect on customer satisfaction.